2008
DOI: 10.1080/10715760801902093
|View full text |Cite
|
Sign up to set email alerts
|

Distinct H2O2concentration promotes proliferation of tumour cells after transient oxygen/glucose deprivation

Abstract: A solid tumour undergoes ischemia/reperfusion due to deficient vascularization and subsequent formation of new blood vessels. This study investigated the effect of transient oxygen and glucose deprivation (OGD) on proliferation of C6 glioma cells. The cells were subjected to 18 h of OGD followed by reoxygenation in the presence of glucose and different extra-cellular H(2)O(2) concentrations since H(2)O(2) affects cell proliferation. After reoxygenation, the cellular H(2)O(2) concentration was increased returni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The overexpression of SOD2 can also induce increased levels of hydrogen peroxide (H2O2) [40,41]. H2O2 is a major intracellular oxidant and induces DNA damage in glioma cells [42,43]. Although it might be difficult to determine the precise mechanisms that are most relevant to the pathologies of the patients in this study, the identification of these two possible mechanisms is consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
“…The overexpression of SOD2 can also induce increased levels of hydrogen peroxide (H2O2) [40,41]. H2O2 is a major intracellular oxidant and induces DNA damage in glioma cells [42,43]. Although it might be difficult to determine the precise mechanisms that are most relevant to the pathologies of the patients in this study, the identification of these two possible mechanisms is consistent with our results.…”
Section: Discussionsupporting
confidence: 81%
“…Besides their well-known toxic effects, ROS/NO could be responsible for the modulation of various cellular functions under normal conditions (26). Recent reports demonstrated that ROS play an important role in proliferation of proliferative cells (27,28). Using ROS scavengers and an NADPH oxidase inhibitor, our previous study showed that proliferative activity is positively regulated by ROS, which are endogenously generated by activation of NADPH oxidase throughout the cell proliferation of embryonic hippocampal NPCs (15).…”
Section: Endogenous Generation Of Ros/nomentioning
confidence: 99%
“…Therapeutic treatments based on adjusting the intracellular H 2 O 2 levels have been investigated. [114][115][116] In this subsection, we focus on therapeutic approaches based on MOFs that are responsive to H 2 O 2 in tumors.…”
Section: H 2 Omentioning
confidence: 99%